2020
DOI: 10.1002/cncr.32913
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma with isolated lymph node metastases should be reclassified as stage IV

Abstract: On the basis of institutional and population‐based data, it has become clear that the risk of progression is distinctly different for lymph node–positive (LN+)/M0 renal cell carcinoma in comparison with locally advanced, nonmetastatic renal cell carcinoma. It is critical that the American Joint Committee on Cancer staging system recognize the increased risk with LN+/M0 tumors and consider reclassification of LN+/M0 as stage IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In all, 204 patients with sRCC and 217 with Grade 4 non-sRCC had recurrence data available. The median (95% CI) RFS between sRCC and non-sRCC was 14 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) months compared to 23 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) months, respectively (P = 0.059; Fig. 1).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In all, 204 patients with sRCC and 217 with Grade 4 non-sRCC had recurrence data available. The median (95% CI) RFS between sRCC and non-sRCC was 14 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) months compared to 23 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) months, respectively (P = 0.059; Fig. 1).…”
Section: Resultsmentioning
confidence: 97%
“…Most importantly, if our localised sarcomatoid survival results are confirmed, amending current staging systems to better represent the poor prognostic presence of sRCC is reasonable. Indeed, this is not the first time traditional TNM staging has been questioned [23,24]. In 2007, criticism was rendered of then-current 2002 AJCC staging guidelines for locally advanced RCC as it failed to incorporate 'alternative clinicopathologic factors important in RCC prognosis' such as histological subtype, presence of necrosis and, interestingly, sarcomatoid features [24].…”
Section: Discussionmentioning
confidence: 99%
“…[79] Daniel et al suggested the reclassification of RCC with isolated LN metastases to stage IV to enable more precise baseline risk stratification for patients with LNM-RCC. [80] Given the current lack of robust and consistent evidence from retrospective studies on LND, further research is imperative to evaluate the efficacy of LND and to improve the stratification of patients, identifying those who may derive benefit from the intervention.…”
Section: The Site Of Rcc Metastasismentioning
confidence: 99%